Properties of hydrated mineral trioxide aggregate - Tanomaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Springer Nature, 2014)
Mineral trioxide aggregate (MTA) is composed of Portland cement and bismuth oxide as radiopacifying material. This chapter aimed at discussing the physicochemical and biological properties of MTA. When MTA is mixed with water, it hydrates to form a solid structure after 2-3 h. MTA has a compressive strength, which increases with time, and the adhesion and microhardness of the material are satisfactory and can be influenced by several factors. MTA exhibits slight expansion after setting. Most of the studies demonstrate that MTA is not soluble or presents low solubility when immersed in solution. MTA exhibits adequate sealing and has limited antimicrobial effect against some microorganisms. MTA might cause dental discoloration, which can compromise aesthetics. The amount of heavy metals released by MTA is a common concern with respect to the clinical application. In vitro studies have shown that MTA is biocompatible. Clinical research assessing the various uses of MTA compared to other standard materials has shown comparable clinical outcomes for all the materials tested.